1999
DOI: 10.1038/sj.bjc.6690579
|View full text |Cite
|
Sign up to set email alerts
|

hMSH2 and GTBP expression in advanced stage epithelial ovarian cancer

Abstract: Summary Defects in DNA mismatch repair have been associated with both hereditary and sporadic forms of human cancer. Most of the attention has been focused on the incidence and genetics of mismatch repair defects, while little is known about the expression levels of the mismatch repair proteins and their significance in cancer cell biology. In this study, both the expression levels of hMSH2 and GTBP proteins were investigated by Western blotting in 20 untreated epithelial ovarian cancers. For these analyses, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…Experimental studies have shown that mismatch repair deficient colon cell lines are tolerant to chemotherapy [16]. Other studies have suggested that also mismatch repair deficient OC cell lines are resistant to chemotherapy [17,18]. One case report supported these findings [19].…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Experimental studies have shown that mismatch repair deficient colon cell lines are tolerant to chemotherapy [16]. Other studies have suggested that also mismatch repair deficient OC cell lines are resistant to chemotherapy [17,18]. One case report supported these findings [19].…”
Section: Introductionmentioning
confidence: 82%
“…In vitro studies suggested an involvement of mismatch repair gene mutations in decreased susceptibility of ovarian cancer cells to cisplatin therapy [17,18]. Standard treatment of OC contains platinum agents.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Among these genes, MSH2 encodes for a DNA-mismatch repair protein that has been previously found to be altered in human solid tumors. [7][8][9] Considering that evaluation of MSH2 expression in cytological specimens has been reported only in metastatic to lymph nodes and liver melanomas, 10 in this study, we have analyzed by immunocytochemistry the expression of MSH2 DNA-repair protein in a bank of cytological material obtained by fine needle aspiration (FNA) from patients diagnosed with lung adenocarcinoma, small cell carcinoma, or squamous cell carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Identifying epithelial ovarian tumors with MMR defects is not only important for early detection of women with Lynch syndrome, but may also have treatment implications. Several in-vitro studies and a small case series also suggest a relation between MMR gene mutations and decreased susceptibility to cisplatin, a common chemotherapeutic agent used to treat ovarian carcinomas (14)(15)(16)(17)(18). Several in-vitro studies and a small case series also suggest a relation between MMR gene mutations and decreased susceptibility to cisplatin, a common chemotherapeutic agent used to treat ovarian carcinomas (14)(15)(16)(17)(18).…”
mentioning
confidence: 99%